Exploring the Consistency of Data Collected in Archaeological Geophysics: A Case Study from the Iron Age Hillfort of Villasviejas del Tamuja (Extremadura, Spain) - Pro, C. (2022)
Different geophysical methods applied at the settlement of Villasviejas del Tamuja (Botija, Spain) have identified robust anomalies located at the same position, but some anomalies are reflected by only one method. Furthermore, analysing the spatial correlation of these anomalies is of fundamental importance for obtaining a correct archaeological interpretation. In this work, we analysed the main results of electrical resistivity tomography (ERT), ground-penetrating radar (GPR) and magnetic gradiometry methods in a particular area of the archaeological site. In this analysis, we performed graphical and numerical spatial correlation analyses of the anomalies and observed strong agreement among the results provided by each method. Certain anomalies were reflected only in the magnetic and ERT studies. The results highlight the importance of applying several geophysical methods and performing spatial correlational analyses. Furthermore, the methodology that we have applied to evaluate the spatial correlation offers interesting results.